The rapid antidepressant effect of acupuncture on two animal models of depression by increasing the expression of synaptic proteins in the prefrontal cortex - Bai-le NING; Zhi-fang WANG; Qing YANG; Qian WU; Qi-yue DENG; Jing GAO; Wen FU; Ying DENG; Bing-xin WU; Xi-chang HUANG; Cong WANG; Wen-bin FU (World Journal of Acupuncture - Moxibustion)
Objective: To investigate the effect of acupuncture onset time and synaptic structure in two different models of depression. Methods: A total of 150 healthy male adult SPF C57BL/6J mice were divided into five time-point groups: 1 h, 3 h, 6 h, 12 h and 24 h. Each time-point group was further divided into three groups: the model, scopolamine and acupuncture groups with 10 rats each. Rats were given forced swimming stimulation (15 min, once) before the intervention. A total of 200 healthy male adult specific pathogen-free (SPF) Sprague-Dawley (SD) rats were divided into 30 normal rats, and 170 modelling ones. A total of 90 rats were successfully modeled, and were randomly divided into three time-point groups: 1 h, 6 h and 24 h. And each time-point group was further divided into the normal, model, scopolamine, and acupuncture group. Chronic unpredictable mild stress (CUMS) combined with individual feeding was used to establish the depressed rat model. The sucrose preference test (SPT) and open field test (OFT) were used to evaluate the success of the model. There were 10 rats in each group. The acupuncture intervention was performed once for 20 min on “Baihui (GV20)”, “Yintang (GV29)”, “Hegu (LI4)”, and “Taichong (LR3)” without any other operations for the corresponding animals. Other groups were given corresponding medications. According to different time points, the forced swimming test (FST) was conducted in mice, and the FST and novelty-suppressed feeding test (NSFT) were measured in rats. Monoamine neurotransmitters (NE, DA, DOPAC, 5-HT, 5-HIAA, HVA) in the prefrontal cortex and hippocampus were detected with high performance liquid chromatography (HPLC). The expression of synapsin I, PSD95, p-mTOR, mTOR, and BDNF in the prefrontal cortex and hippocampus was determined by western blot. Results: At the 1 h time point, compared with the model group, the immobility time was significantly decreased in the acupuncture group (P < 0.05). At 3 h, 6 h, 12 h, and 24 h, compared with the model group, the immobility time was significantly reduced in both scopolamine and acupuncture groups (P < 0.05). At the 1 h time point, compared with the normal group, the immobility time of FST and the latency to feed were significantly increased in the model group (P < 0.05). Compared with the model group, the immobility time of FST showed a significant reduction in the acupuncture group (P < 0.05). At the 6 h and 24 h time points, compared with the normal group, the immobility time of FST and the latency to feed were significantly increased in the model group (P < 0.05). Compared with the model group, the immobility time of FST was significantly decreased in the scopolamine and acupuncture groups (P < 0.05). At the 1 h and 24 h time points, compared with the normal group, the expression levels of 5-HT, 5-HIAA, NE, DA, DOPAC, and HVA of the prefrontal cortical and hippocampal tissues were significantly reduced in the model group (P < 0.05). At the 1 h and 24 h time points, compared with the model group, the expression levels of synapsin I, PSD95, p-mTOR, and BDNF of the prefrontal cortex were significantly increased in the acupuncture group (P < 0.05). At the 1 h and 24 h time points, compared with the normal group, the expression levels of synapsin I, PSD95, p-mTOR, and BDNF of the prefrontal cortex were significantly reduced in the model group (P < 0.05). Compared with the model group, the expression levels of synapsin I, PSD95, p-mTOR, and BDNF of the prefrontal cortex were significantly increased in the acupuncture group (P < 0.05). At the 1 h and 24 h time points, compared with the normal group, the expression levels of synapsin I, PSD95, p-mTOR, and BDNF of the hippocampal tissues were significantly reduced in the model group (P < 0.05). Compared with the model group, the expression levels of synapsin I, PSD95, p-mTOR, and BDNF of the hippocampus were not significantly different in the acupuncture group (P > 0.05). Conclusion: Acupuncture may play a rapid antidepressant effect by increasing the expression of synaptic plasticity proteins in the prefrontal cortex.